Multi-Omics Analysis in Initiation and Progression of Meningiomas: From Pathogenesis to Diagnosis - Liu, Jiachen; Xia, Congcong; Wang, Gaiqing (Frontiers in Oncology, 2020)
Meningiomas are relatively common, and typically benign intracranial tumors, which in many cases can be cured by surgical resection. However, high-grade meningioma, which grows quickly, and recurs frequently despite multimodal treatment, leading to poor patient outcomes. Therefore, the early diagnosis and classification of meningioma is very important for the subsequent intervention and prognosis. A growing body of evidence demonstrates the potential of multi-omics study (including genomics, transcriptomics, epigenomics, proteomics) for meningiomas diagnosis and mechanistic links to underlying therapeutic targets. This thesis addresses a neglected aspect of recent advances in the field of meningiomas at multiple omics levels, highlighting the integration of multi-omics enables uncovering the mechanism of meningiomas at a system level. The review provides a timely and necessary study of the scientific basis for further treatment of meningiomas.